Neurosurgery case review questions and answers - Nader, Remi; Sabbagh, Abdulrahman J.; Elbabaa, Samer K.; Al-Jehani, Hosam; Gasco, Jaime; Gragnaniello, Cristian (Thieme, 2020)
"Neurosurgery Case Review: Questions and Answers, 2nd Edition by Remi Nader, Abdulrahman Sabbagh, Samer Elbabaa, Hosam Al Jehani, Jaime Gasco, and Cristian Gragnaniello provides a robust study guide for the American Board Neurological Surgery and the Royal College of Physicians and Surgeons of Canada oral board examinations. The second edition expands on the highly successful first edition, presenting 148 cases commonly encountered by neurosurgeons in clinical practice. The cases are broadly divided into seven sections-tumor, vascular intracranial pathology, trauma, pediatric, functional, spine, and peripheral nerves. The chapters are arranged in a manner that mirrors the oral board exam. Each case includes a brief clinical scenario followed by questions on presentation, diagnosis, imaging, management, surgical detail, complications, and outcome. The presented information is backed by the latest available evidence-based references and data. Key Features: Contributions from internationally renowned neurosurgical educators Detailed answers enhance readers' knowledge and provide guidance on how to respond to questions asked in the oral board exams More than 760 high-quality images, many in full color, ensure visual understanding of key concepts Suggested readings at the end of cases offer additional study resources This is an indispensable, one-stop resource for neurosurgical residents and fellows prepping for the ABNS and Royal College oral board examinations. Neurosurgeons studying for recertification will also find this book an invaluable reference for rapid review"--